2022
DOI: 10.1038/s41533-022-00297-5
|View full text |Cite
|
Sign up to set email alerts
|

Practical tips in bronchiectasis for Primary Care

Abstract: Bronchiectasis is the third most common chronic inflammatory airway disease, after chronic obstructive pulmonary disease (COPD) and asthma with a prevalence clearly underestimated probably because of its clinical similitudes with other chronic airway diseases. Bronchiectasis can be caused by a dozen of pulmonary and extra-pulmonary diseases and a variable number and severity of exacerbations can appear throughout its natural history, usually with an infectious profile. The dilation of the airway and the inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The clinical overlap between the multiple respiratory affections, the heterogeneous clinical presentation, and the frequently inadequate radiological interpretation lead to the misdiagnosis and underdiagnoses of NCFB [ 10 ]. Although the exact epidemiology of NCFB is still unknown, different authors have reported increasing prevalence and incidence rates of NCFB during the last three decades.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical overlap between the multiple respiratory affections, the heterogeneous clinical presentation, and the frequently inadequate radiological interpretation lead to the misdiagnosis and underdiagnoses of NCFB [ 10 ]. Although the exact epidemiology of NCFB is still unknown, different authors have reported increasing prevalence and incidence rates of NCFB during the last three decades.…”
Section: Introductionmentioning
confidence: 99%